2014
DOI: 10.1161/circinterventions.113.000988
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Short-Term Readmission After Percutaneous Coronary Intervention

Abstract: R eadmission after inpatient hospitalization is common and costly. According to an analysis of Medicare claims data, 19.6% of Medicare patients discharged after a hospital admission during which percutaneous coronary intervention (PCI) is performed are readmitted within 30 days, and the Medicare Payment Advisory Commission has estimated that preventable readmissions cost Medicare as much as $12 billion per year. 1 The Affordable Care Act has created financial penalties for hospitals that have risk-adjusted rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 8 publications
6
65
3
Order By: Relevance
“…Our checklist, in contrast, was designed to be implemented at the time of discharge and addresses previous research on the causes and preventability of PCI readmissions. 11 The checklist for post-PCI patients includes a sublingual nitroglycerin prescription and confirmation of insurance coverage of prescribed antiplatelet agents. The checklist also recommends timely follow-up, especially for patients at high risk for readmission either by the readmission risk score or by the subjective assessment of the clinician.…”
Section: During Hospitalizationmentioning
confidence: 99%
“…Our checklist, in contrast, was designed to be implemented at the time of discharge and addresses previous research on the causes and preventability of PCI readmissions. 11 The checklist for post-PCI patients includes a sublingual nitroglycerin prescription and confirmation of insurance coverage of prescribed antiplatelet agents. The checklist also recommends timely follow-up, especially for patients at high risk for readmission either by the readmission risk score or by the subjective assessment of the clinician.…”
Section: During Hospitalizationmentioning
confidence: 99%
“…First are tactics that are likely to appropriately triage and evaluate patients with chest discomfort after PCI. We previously have shown that improved access to cardiology care in the emergency department can reduce unnecessary readmissions for low‐risk chest discomfort after PCI 6. Other strategies include reducing risk of infection and gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…After the passage of HRRP as part of health reform in 2010, large analyses of administrative data have shown that readmission rates after AMI decreased faster than they had been decreasing before the law 4, 5, 6. Because distinguishing these types of different patients with AMI is difficult from administrative data, it is not known what specific tactics have reduced readmissions or could further improve performance in the future.…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis within the Partners Healthcare system in Boston, Massachusetts, demonstrated compatible results with only 6.7% of readmissions related to procedural complications and 38.1% of readmissions for chest discomfort or other symptoms concerning for angina without immediately obvious stent thrombosis. 13 Detailed adjudication of those cases revealed that only 2.6% of those patients with chest discomfort underwent target lesion revascularization (TLR) despite 84.4% of patients undergoing at least one diagnostic procedure during the readmission. 13 …”
Section: Limitations Of the Pci Readmission Performance Metricmentioning
confidence: 99%
“…13 Detailed adjudication of those cases revealed that only 2.6% of those patients with chest discomfort underwent target lesion revascularization (TLR) despite 84.4% of patients undergoing at least one diagnostic procedure during the readmission. 13 …”
Section: Limitations Of the Pci Readmission Performance Metricmentioning
confidence: 99%